2021
DOI: 10.1039/d0nr09133b
|View full text |Cite
|
Sign up to set email alerts
|

A palladium doped 1T-phase molybdenum disulfide–black phosphorene two-dimensional van der Waals heterostructure for visible-light enhanced electrocatalytic hydrogen evolution

Abstract: The electrocatalytic hydrogen evolution reaction (HER) is a green chemistry route for sustainable energy production. Compared to 2H-phase molybdenum disulfide (MoS2), the 1T-phase MoS2 (1T-MoS2) have higher theoretical activity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In detail, the lattices with d spacing of 0.70 and 0.27 nm are attributed to the (002) and (100) planes of 1T MoS 2 , which are equal to those in the literature. 36,37 The S vacancies in the structure of the composite-materials were observed, typically consisting of cracks and misaligned basal planes (Fig. 2f and S4 †).…”
Section: Morphology and Characterization Of Composite-materialsmentioning
confidence: 99%
“…In detail, the lattices with d spacing of 0.70 and 0.27 nm are attributed to the (002) and (100) planes of 1T MoS 2 , which are equal to those in the literature. 36,37 The S vacancies in the structure of the composite-materials were observed, typically consisting of cracks and misaligned basal planes (Fig. 2f and S4 †).…”
Section: Morphology and Characterization Of Composite-materialsmentioning
confidence: 99%
“…121 Recently, it has been reported that van der Waals heterostructure of Pd dopped 1T-MoS 2 and BP nanosheet exhibits increased light absorption when compared to Pd-1T-MoS 2 . 97 Under the light irradiation, the composite shows a decrease in the overpotential from 152 mV to 97 mV at the current density of 10 mA cm À2 with a concomitant decrease in the Tafel slope from 86 mV dec À1 to 66 mV dec À1 . Furthermore, BP quantum dots (BPQDs) have the capability of harvesting the full visible light spectrum due to sizedependent bandgaps.…”
Section: Photo-electrocatalysis (Pec)mentioning
confidence: 94%
“…As shown in Figure c, the improvement in HER activity is not primarily due to an increase in active sites. The impact of Pd doping on HER activity was assessed by further calculating the differential charge density and hydrogen adsorption free energy (Δ G H* ) as shown in Figure d-e …”
Section: Doping Strategymentioning
confidence: 99%